Human T follicular helper cells and their impact on IgE and IgG4 production across allergy, malignancy, and IgG4-related disease - Mitsuhiro Akiyama; Waleed Alshehri; Sho Ishigaki; Koichi Saito; Yuko Kaneko (Allergology International)
Human T follicular helper (Tfh) cells play a crucial role in orchestrating B cell differentiation, maturation, and immunoglobulin class switching. Recent studies have underscored the presence of Bcl-6 + Tfh cells not only in secondary lymphoid organs but also within tertiary lymphoid structures at inflammatory sites, emphasizing their pivotal role in disease pathogenesis. Furthermore, Tfh cells have been found to transit between lesion sites, lymph nodes, and peripheral blood, as revealed by T cell receptor repertoire analysis. Among Tfh subsets, Tfh2 cells have emerged as central orchestrators in driving the production of IgE and IgG4 from B cells. Their critical role in diseases such as allergy, malignancy, and IgG4-related disease highlights their profound impact on balancing inflammation and immune tolerance. Our current review provides the molecular characteristics of human Tfh cells, the differentiation pathways of Tfh subsets, mechanisms by which Tfh subsets induce IgE and IgG4 production, and their clinical implications in allergy, malignancy, and IgG4-related disease.